2013
DOI: 10.1558/wap.v5i1.83
|View full text |Cite
|
Sign up to set email alerts
|

What Vocabulary Should We Teach?

Abstract: Multiple studies on the relationship between lexical diversity and holistic writing quality in a second language (L2) have consistently shown that a greater number of unique lexical items, compared to the total number of words, is associated with better quality writing. The findings of such studies indicate the importance of vocabulary to L2 writing. However, they provide little information in terms of what vocabulary L2 writers need to learn in order to improve their writing. Despite its limited application i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…The handful of studies using lexical frequency profiles to analyze L2 writers' texts have found that the use of vocabulary that appears less frequently in the English language—usually measured as decreased use of words from the 1K and 2K GSL list and increased use of words from the AWL or UWL and from beyond the 2K GSL list—is associated with L2 writing development over time as well as L2 writing performance (Laufer, ; Laufer & Nation, ). More recent studies using frequency lists based on the Bank of English corpus (Coniam, ), British National Corpus (Johnson, Acevedo, & Mercado, ), or specialty frequency lists generated from the participants' own writing (Verspoor, Schmid, & Xu, ) appear to support the findings of earlier studies using the GSL and UWL or AWL. To summarize the findings of these studies concisely, the use of words that appear less frequently in the English language is associated with stronger L2 writing performance as well as L2 writing development over time.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…The handful of studies using lexical frequency profiles to analyze L2 writers' texts have found that the use of vocabulary that appears less frequently in the English language—usually measured as decreased use of words from the 1K and 2K GSL list and increased use of words from the AWL or UWL and from beyond the 2K GSL list—is associated with L2 writing development over time as well as L2 writing performance (Laufer, ; Laufer & Nation, ). More recent studies using frequency lists based on the Bank of English corpus (Coniam, ), British National Corpus (Johnson, Acevedo, & Mercado, ), or specialty frequency lists generated from the participants' own writing (Verspoor, Schmid, & Xu, ) appear to support the findings of earlier studies using the GSL and UWL or AWL. To summarize the findings of these studies concisely, the use of words that appear less frequently in the English language is associated with stronger L2 writing performance as well as L2 writing development over time.…”
supporting
confidence: 54%
“…The sample sentence is followed by four alternatives, from which the student must choose the alternative that most closely matches the meaning of the key word. Based on the results of previous research among learners in the same instructional context (Johnson et al., ), the participants were tested only on 1K through 5K word families.…”
Section: Methodsmentioning
confidence: 99%
“…Anecdotally, it may seem that the use of low‐frequency (or sophisticated) words implies lexical diversity. However, there are indications that an essay can demonstrate a diverse use of words without using rarer, less frequently occurring words (Johnson, Acevedo, & Mercado, ; Laufer, ). The main aim, therefore, of this preliminary study is to expand on this seemingly contradictory finding in order to answer the pedagogical question of how best to incorporate vocabulary instruction into writing courses.…”
mentioning
confidence: 99%
“…Rather, attention to students' (a) use of target vocabulary, (b) formation of target vocabulary, and (c) manipulation of target vocabulary (Johnson et al, 2016) is vital to vocabulary acquisition among high school-aged ELLs. In considering productive vocabulary knowledge, teachers should use frequency information to balance two objectives which seem to contradict one another: (a) mastery over accurate productive knowledge of high frequency word families (Johnson et al, 2016), and (b) use of low frequency word families (Johnson et al, 2016), particularly among ELLs from Romance language backgrounds (Johnson et al, 2013).…”
Section: Pedagogical Implicationsmentioning
confidence: 99%
“…Yet much of the literature from educational research examines vocabulary instruction in K-5 instructional contexts, typically in English Language Arts, and typically using children's literature (Austermuehle, Kautz, & Sprenzel, 2007;Beck et al, 2005;Boulware-Gooden, Carreker, Thornhill, & Joshi, 2007;Calderόn et al, 2005;Cunningham & Stanovich, 1991). Further, such research appears to focus on vocabulary instruction as a means to text comprehension, despite (a) conceptions of vocabulary knowledge as multifaceted (Nation, 2001), and (b) research evidence to suggest productive knowledge of low-frequency vocabulary is associated with written L2 performance (Johnson, Acevedo, & Mercado, 2013, 2016. How then, are mainstream high school teachers to choose vocabulary for instruction to ELLs in their classes?…”
mentioning
confidence: 99%